Social Networking, and firm performance: Mediating role of comparative advantage and sustainable supply chain - A. Harits Nu'man; Luthfi Nurwandi; Iyan Bachtiar; Tasya Aspiranti; Ikbar Pratama (International Journal of Supply Chain Management, 2020)
The key objective of the current study is to examine the role of social networking in determining the firm performance of manufacturing firms. Addition to this the study has studied the mediating role of comparative advantage and sustainable supply chain in the relationship between the social networking and firm performance of manufacturing firms. The basic concern of this research is to examine the way in which performance is generated and achieve by firms. Several theoretical approaches have been used for analyzing the relation between existing resources and performance of a firm. The relation between entrepreneurial orientation and firm performance has been explained using RBV theory by incorporating moderator and mediator variables. The results were presented for the model using PLS because of its flexibility, validity, and estimation of complex models. PLS-SEM method is also known as second general approach of SEM. In this study, the response rate of 77.6% is sufficient because 30% response rate was regarded sufficient by Dikko [1] in survey studies. These positive influences of SCM capability are supported by social capital theory. Relational and structural capitals are accumulated through collaboration, information sharing, mutual trust, communication, and commitment among the partners in the supply chain. These create improvement in the performance of suppliers and buyers.